2006
DOI: 10.1007/s10517-006-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on the relationship between lipid peroxidation and proteolytic activity in basal nuclei of rat brain during acute hypoxia

Abstract: We studied the effect of melatonin on the relationship between LPO intensity and proteolytic activity in basal nuclei (caudate nucleus, globus pallidus, amygdaloid complex, and nucleus accumbens septi) of rat brain during acute hypobaric hypoxia. Acute hypoxia was accompanied by LPO activation and increase in proteolytic activity. It should be emphasized that the intensity of proteolysis was higher in structures responding by more pronounced LPO activation (nucleus accumbens septi and globus pallidus). Intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This is in consistent with our previous studies showing the protective effect of melatonin against CIH-induced neuronal and cardiac injuries [7,8]. The known neuroprotective effect of melatonin is, in part, attributed to its antioxidant property against the lipid peroxidation in the central nervous system during oxidative insults [49,50,51]. In fact, melatonin, which directly scavenges ROS, also reduces lipid peroxidation indirectly through mediating an up-regulation of the expression of antioxidant enzymes [52,53].…”
Section: Discussionsupporting
confidence: 92%
“…This is in consistent with our previous studies showing the protective effect of melatonin against CIH-induced neuronal and cardiac injuries [7,8]. The known neuroprotective effect of melatonin is, in part, attributed to its antioxidant property against the lipid peroxidation in the central nervous system during oxidative insults [49,50,51]. In fact, melatonin, which directly scavenges ROS, also reduces lipid peroxidation indirectly through mediating an up-regulation of the expression of antioxidant enzymes [52,53].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, lipid peroxidation is one of the major processes mediating the breakdown of membrane lipids leading to neuronal injury [40, 41]. It has been suggested that the neuroprotective effect of melatonin could be attributed to the antioxidant property, which prevents the lipid peroxidation in the central nervous system during oxidative insults [42–44]. This is supported by results of this study and also by our recent observation that melatonin mitigates IH‐induced oxidative stress and prevents inflammation and apoptosis in the hippocampus [30].…”
Section: Discussionmentioning
confidence: 99%